Immunomodulation as a Novel Strategy for Prevention and Treatment of Bordetella spp. Infections - Gestal, Monica C.; Johnson, Hannah M.; Harvill, Eric T. (Frontiers in Immunology, 2019)
Well-adapted pathogens have evolved to survive the many challenges of a robust immune response. Defending against all host antimicrobials simultaneously would be exceedingly difficult, if not impossible, so many co-evolved organisms utilize immunomodulatory tools to subvert, distract and/or evade the host immune response. Bordetella spp. present many examples of the diversity of immunomodulators and an exceptional experimental system in which to study them. Recent advances in this experimental system suggest strategies for interventions that tweak immunity to disrupt bacterial immunomodulation, engaging more effective host immunity to better prevent and treat infections. Here we review advances in the understanding of respiratory pathogens, with special focus on Bordetella spp., and prospects for the use of immune-stimulatory interventions in the prevention and treatment of infection.